Co–Nx catalyst: an effective catalyst for the transformation of nitro compounds into azo compounds. Issue 1 (13th October 2020) - Huang, Renjie; Wang, Yanxin; Liu, XiXi; Zhou, Peng; Jin, Shiwei; Zhang, Zehui
Abstract : The selective hydrogenation of nitro compounds into their corresponding azo compounds is challenging in organic synthesis. Abstract : The selective hydrogenation of nitro compounds into their corresponding azo compounds is challenging in organic synthesis. In this study, we have developed a facile and efficient catalytic system for the transformation of nitro compounds into azo compounds under mild conditions over a heterogeneous cobalt catalyst (Co–N x /C-800-AT). The Co–N x /C-800-AT catalyst was found to be highly active for the reductive-coupling of nitro compounds into azo compounds in ethanol at 110 °C and 2.5 bar H2 pressure with the addition of NaOH as an additive, affording structurally-diverse azo compounds with satisfactory yields (70.4–98.3%). The developed method demonstrated several advantages such as high catalytic activity and high selectivity with tolerance to other functional groups and high stability.